Comprehensive phenotypic assessment of nonsense mutations in mitochondrial ND5 in mice - Sanghun Kim; Seul Gi Park; Jieun Kim; Seongho Hong; Sang-Mi Cho; Soo-Yeon Lim; Eun-Kyoung Kim; Sungjin Ju; Su Bin Lee; Sol Pin Kim; Tae Young Jeong; Yeji Oh; et al. (Experimental and Molecular Medicine)
Abstract Mitochondrial dysfunction induced by mitochondrial DNA (mtDNA) mutations has been implicated in various human diseases. A comprehensive analysis of mitochondrial genetic disorders requires suitable animal models for human disease studies. While gene knockout via premature stop codons is a powerful method for investigating the unique functions of target genes, achieving knockout of mtDNA has been rare. Here, we report the genotypes and phenotypes of heteroplasmic MT-ND5 gene-knockout mice. These mutant mice presented damaged mitochondrial cristae in the cerebral cortex, hippocampal atrophy, and asymmetry, leading to learning and memory abnormalities. Moreover, mutant mice are susceptible to obesity and thermogenetic disorders. We propose that these mtDNA gene-knockdown mice could serve as valuable animal models for studying the MT-ND5 gene and developing therapies for human mitochondrial disorders in the future.